Mini review: Promotion of substance abuse in HIV patients: Biological mediation by HIV-1 Tat protein. (14th May 2021) - Cirino, Thomas J.; McLaughlin, Jay P.
Highlights: Substance use disorder (SUD) remains highly comorbid in patients living with HIV. SUD exacerbates the progression of HIV, but impact of HIV on drug reward unclear. HIV-1 Tat protein potentiates the rewarding effects of abused drugs in animals. Exposure to HIV-1 Tat protein sufficiently induces drug relapse in abstinent mice. Neurochemical activity of HIV-1 Tat protein excites brain reward circuitry. Abstract: Despite successful viral suppression by combinatorial anti-retroviral therapy, HIV infection continues to negatively impact the quality of life of patients by promoting neuropathy and HIV-Associated Neurocognitive Disorders (HAND), where substance use disorder (SUD) is highly comorbid and known to worsen health outcomes. While substance abuse exacerbates the progression of HIV, emerging evidence also suggests the virus may potentiate the rewarding effect of abused substances. As HIV does not infect neurons, these effects are theorized to be mediated by viral proteins. Key among these proteins are HIV-1 Tat, which can continue to be produced under viral suppression in patients. This review will recap the behavioral evidence for HIV-1 Tat mediation of a potentiation of cocaine, opioid and alcohol reward, and explore the neurochemical dysfunction associated by Tat as potential mechanisms underlying changes in reward. Targeting rampant oxidative stress, inflammation and excitotoxicity associated with HIV and Tat protein exposure may prove useful in combating persistent substance abuse comorbid with HIV in the clinic.